Os lugares de produção da história militar: historiadores militares no Estado Novo - Oliveira, Priscila Roatt de (2015)
The main problem of this work is to understand the political sense of the rememoration of the past inside the Brazillian Armed Forces and in which ways the historiographical production of this institution collaborated to create a form of speech that justifies its own political and social finality in the New State period. Furthermore, how these narratives about the past of the institution collaborated to create some sort of identity to the soldiers in this period. The present work analyze the historiography produced by a group of individuals, from the civil society or military that had connections with the Brazillian Armed Forces. This work used three sources of historiographical production: Biblioteca Militar (Military Library), A Defesa Nacional ( The National Defense magazine), Revista Nação Armada (Armed Nation Magazine), all of them having bonds to the army or/and having military writers with close relations with the Getúlio Vargas government. There was two themes highlighted in the military production: the biographical narratives and the anti-communism. This work discusses on how these biographical narratives transformed the heroes life into moral examples. The glorification of the hero as a form of identification of the Army in the New State period, but also the opposite: the traitor. This concept was associated to the communists, after the uprisings from the Aliança Nacional Libertadora (National Alliance of Liberation) in 1935. In the second part of this work, there is a discussion about the place that the Brazillian Armed Forces occupies in the nationality formation in the past, present and future of the nation, using the narratives from the Military Library and Military magazines. This work belongs to the Post-Graduation Program in History at the Santa Maria Federal University, in the Culture, Power and History research field, in the Society, Politics and Frontier line. It got a CAPES scholarship.